Neuroimmune Pharmacology as an Emerging Curriculum for Pre-Medical Students - Buch, Shilpa J. (J Neuroimmune Pharmacol, 2010)
As science continues to evolve and expand some major areas of interest are now crossing boundaries to become multi-disciplinary in nature closely reflecting the biological processes of the organism as a whole. The fields of neuroscience, immunology, and pharmacology are good examples of one such emerging inter-disciplinary area. This article is focused on developing a curriculum for undergraduate pre-medical students in the area of neuroimmune pharmacology (NIP) to empower them with the knowledge of neuroscience and its interaction with immune responses and drug interactions. This course is intended to amalgamate and put into perspective a large body of knowledge including: (1) brain function in health and disease, (2) cross talk between neural and immune responses, and (3) the pharmacology of drugs of abuse in the context of neurodegenerative diseases. The goal of this course is to expose pre-medical students to the field of NIP so that they are equipped with a solid foundation in these multidisciplinary fields for future clinical/academic careers.